Dereplication of Gambierdiscusbalechii extract by LC-HRMS and in vitro assay: First description of a putative ciguatoxin and confirmation of 44-methylgambierone. (April 2023) - Tartaglione, Luciana; Loeffler, Christopher R.; Miele, Valentina; Varriale, Fabio; Varra, Michela; Monti, Marcello; Varone, Alessia; Bodi, Dorina; Spielmeyer, Astrid; Capellacci, Samuela; Penna, Antonella; Dell'Aversano, Carmela
Abstract: Marine toxins have a significant impact on seafood resources and human health. Up to date, mainly based on bioassays results, two genera of toxic microalgae, Gambierdiscus and Fukuyoa have been hypothesized to produce a suite of biologically active compounds, including maitotoxins (MTXs) and ciguatoxins (CTXs) with the latter causing ciguatera poisoning (CP) in humans. The global ubiquity of these microalgae and their ability to produce (un-)known bioactive compounds, necessitates strategies for screening, identifying, and reducing the number of target algal species and compounds selected for structural elucidation. To accomplish this task, a dereplication process is necessary to screen and profile algal extracts, identify target compounds, and support the discovery of novel bioactive chemotypes. Herein, a dereplication strategy was applied to a crude extract of a G. balechii culture to investigate for bioactive compounds with relevance to CP using liquid chromatography-high resolution mass spectrometry, in vitro cell-based bioassay, and a combination thereof via a bioassay-guided micro-fractionation. Three biologically active fractions exhibiting CTX-like and MTX-like toxicity were identified. A naturally incurred fish extract ( Sphyraena barracuda ) was used for confirmation where standards were unavailable. Using this approach, a putative I/C-CTX congener in G. balechii was identified for the first time, 44-methylgambierone was confirmed at 8.6 pg cell −1, and MTX-like compounds were purported. This investigative approach can be applied towards other harmful algal species of interest. The identification of a microalgal species herein, G. balechii (VGO920) which was found capable of producing a putative I/C-CTX in culture is an impactful advancement for global CP research. The large-scale culturing of G. balechii could be used as a source of I/C-CTX reference material not yet commercially available, thus, fulfilling an analytical gap that currently hampers the routine determination of CTXs in various environmental and human health-relevant matrices. Graphical abstract: Image 1 Highlights: Putative I/C-CTX-1 identified for the first time in a dinoflagellate extract. Confirmation of 44-methylgambierone by LC-HRMS 2 in G. balechii. Interdisciplinary two-tiered approach for the dereplication of toxins. Bio-guided fractionation of G. balechii extract by LC-HRMS and N2a-assay.